Wear and mechanical characterization of Mg-Gr self-lubricating composite fabricated by mechanical alloying - Al-maamari, Azzat Esam Abdulqader; Iqbal, AKM Asif; Nuruzzaman, D. M. (Elsevier, 2019)
In this research, the wear and mechanical responses of pure magnesium-graphite (Mg–Gr) composite have been investigated aiming to get the optimum composition of reinforcement. The composite materials were fabricated by mechanical alloying. The percentage of graphite reinforcement was chosen as 3, 5, 7 and 10wt.% to identify its potential for self-lubricating property under dry sliding conditions. The mechanical properties including hardness, tensile strength and flexural strength of the composites and the base material were tested. The wear tests were conducted by using a pin-on-disc tribometer. The results show that the mechanical properties decrease with increasing graphite content as compared to that of the base material. The wear rate and average coefficient of friction decrease with the addition of graphite and was found to be minimum at 5wt.% graphite reinforcement. The addition of 5wt.% graphite in the composite exhibits superior wear properties as compared to that of the matrix material and other compositions of the Mg–Gr composites.